An Arctic seal in temperate waters: History of the ringed seal (Pusa hispida) in the Baltic Sea and its adaptation to the changing environment. (December 2014) - Ukkonen, Pirkko; Aaris-Sørensen, Kim; Arppe, Laura; Daugnora, Linas; Halkka, Antti; Lõugas, Lembi; Oinonen, Markku Juhani; Pilot, Malgorzata; Storå, Jan
The ringed seal ( Pusa hispida ) is an early immigrant in the Baltic Basin and has since its arrival experienced substantial changes in the climate, salinity and productivity of the Basin. In this paper, we discuss the dispersal and distribution of the ringed seal during different stages of the Baltic Sea in relation to past and ongoing environmental changes. Subfossil ringed seal remains around the Baltic Sea and the Danish Straits were radiocarbon dated in order to map the distribution of the species in different time periods. The δ 13 C data were used in evaluating the changes in the marine character of the Baltic Basin. The sequence of the dates indicates a continuous presence of the species in the Baltic Basin. The earliest ringed seal finds come from the Skagerrak/Kattegat area (Denmark, Swedish west coast) and date to the full glacial period and Baltic Ice Lake. In the Baltic Basin, the species appears in the subfossil record during the Ancylus period, but the main part of the remains date to the Littorina stage. During the Littorina stage, the distribution of the species was at least periodically wider than today, covering also southern parts of the Baltic. The presence of breeding populations in southern parts of the Baltic during the Holocene Thermal Maximum (HTM) indicates that the winters were at least periodically cold enough for winter ice. The changes in the marine influence in the Baltic Basin can be seen in the seal collagen δ 13 C values, which serve as a proxy for qualitative changes in water mass salinity.